“The balance of power is me: 0, Harvey Weinstein: 10”: A Critical Discourse Analysis of the press representation of Hollywood’s biggest sexual harassment scandal - Nikolova, Evelin (Women's Studies International Forum, 2021)
On 5 October 2017, The New York Times published an article in which Harvey Weinstein was accused of sexual harassment by five women. The scandal grew to enormous proportions as more allegations against him followed. This led to the #MeToo and TIME'S UP movements, initiatives to fight sexual harassment in the workplace. Given that media discourse can have an impact on the knowledge, beliefs, attitudes, and behaviours of the public regarding these phenomena (van Dijk 1989), this study adopts a Critical Discourse Studies (CDS) perspective and explores how power and gender inequality are sustained, (re)shaped and/or challenged by focusing on the reporting of the Harvey Weinstein case which - to the author's best knowledge - has not been analysed before in the field of linguistics. It draws from the systemic functional linguistics and the discourse-historical approach and it examines the way the perpetrator, the accusers and the phenomenon of sexual harassment were discursively constructed in five key articles published in the New York Times. The findings differ in a major way from existing research on sexual violence against women in that 1) the perpetrator, Weinstein, was depicted with clear ascription of agency, 2) women victims' voices and feelings were foregrounded, 3) the link between sexual harassment and the social context in which it occurs was discussed.
Keywords: Critical discourse studies; Discourse-Historical Approach; Discursive strategies; Media representation; Myriam; Sexual harassment; Transitivity analysis; Weinstein